Very Large Floating Structure with Stabilized Buoyancy Control Device for Photovoltaic Application - Tan, Chee Sean; Tan, Lai Wai (Recent Trends in Civil Engineering and Built Environment, 2022)
The increase in the global population is speculated to set a similar trend in the energy sector. However, the conventional approach of energy derivation had remained unchanged for more than a century and is causing anthropogenic pollution and climate change. Various sustainable alternative of renewable energy particularly solar energy have been developed and implemented as a part of the global effort to gradually decommission the usage of fossil fuel and in turn, reduce carbon footprint to overcome adverse environmental impacts. Nevertheless, it was reported that in 2018, only 0.37% of total energy used globally is powered by solar energy. Photovoltaic by itself is not feasible enough due to the magnified requirement of land for the installation of the modules, therefore, one of the solutions for the above statement is floating photovoltaic. However, the structure for floating photovoltaic are also restraint by certain limitation which includes but not limited the impact of tidal wave and the salinity of the sea water which will promote structural and mechanical degradation. Characterisation of the relationship between the stability of very large floating structures corresponding to the volumetric displacement of the buoyancy control device will be the focal point of this research. The significance of tidal wave impact will be empirically assessed based on a scaled-down model of buoyancy control device integrated very large floating structure by manipulating the buoyancy of buoyancy control device assisted structure to structure without buoyancy control device under a controlled environment. The fluctuation of the buoyancy control device can be reduced by up to 99.65% when tested against the highest configuration of wave transducer by displacing only 50% of air with water and neutral buoyancy is achieved. This paper study the efficacy of buoyancy control device in stabilising floating platform under distinct hydrology setting.